GP.6 The Impact of Brain Invasion on Intracranial Meningioma Grading. (June 2022) - Rebchuk, AD; Chaharyn, BM; Alam, A; Hounjet, C; Gooderham, PA; Yip, S; Makarenko, S
Abstract : Background: In 2016, the WHO Classification of Brain Tumors included brain invasion as a standalone diagnostic criterion for grade 2 meningioma diagnosis. In this study we explored the impact of this change on the incidence and distribution of meningioma grades. Methods: All cases of meningiomas diagnosed from 2007-2020 at a tertiary care hospital were identified. The distribution of meningioma grades before (WHO 2007) and after (WHO 2016) the introduction of the 2016 WHO criteria were compared. Each case in the 2007 cohort was re-graded according to the 2016 criteria to determine the intra-class correlation (ICC) between grading criteria. Results: Of 814 cases, 532 (65.4%) were in the 2007 WHO cohort and 282 (34.6%) were in the 2016 WHO cohort. There were no differences in the distribution of meningioma grades between cohorts (p=0.11). Upon re-grading, 21 cases (3.9%) were changed. ICC between original and revised grade was 0.92 (95% CIs: 0.91-0.93). Amongst Grade 2 meningiomas with brain invasion, 75.8% had three or more atypical histologic features or an elevated mitotic index. Conclusions: Brain invasion alone has minimal impact on the incidence or distribution of specific meningioma grade tumors, likely due to cosegregation of grade elevating features.